Use of social media in news media coverage of the crisis, disaster, and emergencies in Spain - Mayo Cubero, Marcos (Revista Española de Comunicación en Salud, 2019)
The use of sources of information in news media coverage of the crises is a huge challenge for journalists. This research focuses specifically on the use as an informative source of official social media (those belonging to organizations involved in the management of a crisis) and unofficial social media (victims, affected, citizens, etc.) in emergency and disaster coverage. The data comes from an online survey applied to the directors of the 30 most important media in Spain in the four-mass media studied: television, radio, press and online media. The results show that in journalistic coverage of crises, journalists rely a lot on the information from the official website (Public administrations, Police, Firefighters, Civil Defense, etc.), quite a bit on the one coming from the official social media and little in that provided by the unofficial social media (victims, affected, citizens, etc.). Of all the official social networks analyzed: Facebook is the one that inspires less confidence as a source for journalists, in a current context marked by the risk of fake news and misinformation. Regarding the purpose, most journalists use information from social media to verify news stories and get contacts.